Kontribusi Dukungan Sosial Rekan Kerja terhadap Burnout pada Tenaga Pendidik Selama Masa Pandemi - Athira Novia Putri (Syntax Corporation, 2022)
The renewal of regulations regarding face-to-face procedures in schools has led to high levels of stress for educators because they have to adapt teaching methods to the latest regulations regarding health protocols. In addition, educators also learn to adjust to the surrounding environment. The high level of stress for educators will turn into burnout. One of the factors that can minimize the emergence of burnout is social support. Social support can come from anywhere, one of which is social support from colleagues. This study aims to empirically examine the effect of peer social support on burnout in educators. The data was obtained through the support of the social scale of co-workers and burnout. Respondents of this study found 191 educators consisting of 38 men and 161 women with a mean age of 41.6. The analysis technique used is regression analysis. The results showed that labor support had a significant effect of 3% on burnout. The social support of co-workers has an essential role in explaining burnout behavior in educators. This is due to the colleague's help in lightening the educator's workload that revives the motivation of educators to do their work.